Studi Terorisme di Sulawesi Tengah - Muhammad Nur Ali (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2016)
Poso the center of conflict in Central Sulawesi has been symbiotic to terrorism, so that the critical points of the outside reached at least three border areas. Such as South Sulawesi, Southest Sulawesi, and West Sulawesi. Eventhough, the right answer have not been obtained that weather conflict presents the terrorism or terrorism creates the conflict in Poso, but what appears is that terrorism has formed in Poso. This article focuses on three studies (1) the spirit of ideology, (2) struggle obsession, and (3) network system. The ideological spirit moves the spirit of terrorist in Poso, it is fundamental and radical, the struggle obsession is to transform the established order through delegitimation of goverment power that has causes many anger local terrorist in Poso is not independent because they are realted to extra-local and national terrorist and they even connected to global terrorism network.